Revitalisasi Kerajinan Kampia sebagai Upaya Penguatan Identitas Budaya dan Ekonomi Lokal di Jorong Kuok III Koto Nagari Matua Mudiak - Wannofri Samry; Alex Darmawan; Israr Iskandar; Yudhi Andoni (Warta Pengabdian Andalas, 2025)
The Kampia craft, a traditional weaving of pandan leaves from Jorong Kuok III Koto, Nagari Matua Mudiak, faces sustainability threats due to modernization. This community service program aims to revitalize Kampia art by enhancing artisans' capacities, marketing innovations, and intergenerational education. The program was structured into three phases: preparation, implementation, and mentoring. The first phase included field surveys and the development of a roadmap. The second phase encompassed training in design innovation, product diversification, and branding and marketing strategies. The last phase ensured sustainability through ongoing monitoring and support. As a result, artisans had successfully created innovative products, and the Kampia community has emerged as a collaborative and marketing platform. Workshops and the Kampia Festival effectively showcased and sold 21 products developed from the training sessions. By adopting an integrative approach that combines cultural preservation and creative economy principles, Kampia has the potential to become a cultural icon and a premier local product.